Rancang Bangun Sistem Informasi Administrasi Pada Dadung Gym - Hendra Wijaya; Tony Darmanto; Sandi Tendean (INTEKSIS, 2025)
The rapid development of fitness centers has prompted the need for efficient administrative systems. Dadung Gym in Pontianak faces challenges in managing member data and transactions due to reliance on traditional administrative methods. This study aims to design a mobile-based information system to reduce data processing errors, enhance service quality, and support strategic decision-making. Using an object-oriented approach with UML modeling, the system is developed with Flutter for the application framework, Firebaseas the database, and Visual Studio Code as the development tool. The new system automates data recording and offers features such as membership management, GPS-based attendance, and integrated reporting. Implementation of this mobile-based system is expected to improve service quality, simplify administrative processes, and provide a foundation for future business development at Dadung Gym Pontianak.